Perilaku Produksi Islami pada IMK Produk Halal di Masa Pandemi: - Yusi Gumansari; Nurul Huda; Nova Rini (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
According to the Islamic view, production is a human effort to achieve happiness in the world and the hereafter. The concept of production in Islam must pay attention to the principles according to Islamic Sharia and always maintain maqashid al-Sharia. Factors of production in Islam are generally the same as approaches in conventional economics, but with different perspectives. Production according to Islam must also pay attention to the benefit of the people by considering the alms variable. This paper aims to analyze the application of Islamic production behavior in Micro and Small Industries (IMK) that produce halal products, especially during the current pandemic. The research method used is the case study method, a qualitative research method based on human understanding and behavior based on differences in values, beliefs, and scientific theory, held at Shofura, IMK, a mukena producer located in South Jakarta. Based on the research, Shofura discovered has applied Islamic principles in its production behavior. Shofura is also feeling the impact of the pandemic and is making efforts to survive by focusing on online sales and premium mukena that targets the middle to upper consumer segment. Keywords: Islamic Production Behavior; Production; Small Micro Industry; Halal Products; Pandemic